Belgium : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2003)
This Selected Issues paper analyzes fiscal devolution in Belgium. It examines long-term fiscal strategies for meeting the fiscal burden of population aging. The paper presents estimates of the fiscal costs of population aging in Belgium, and discusses their sensitivity to underlying assumptions. Strategies for meeting the fiscal costs of aging are discussed. Specifically, a strategy of swift debt reduction is discussed to see what budget surplus would be needed to reduce debt and interest payments rapidly enough to finance these costs. Alternative policy options are also discussed to show the consequences of delayed fiscal adjustment.